On democracy - White, E. B. (Elwyn Brooks), 1899-1985 (Harper, an imprint of HarperCollinsPublishers, 2019)
"Anchored by an introduction by Jon Meacham, this concise collection of essays, letters, and poems from one of this country's most eminent literary voices sheds much-needed historical context on the state of the nation and offers a ray of hope for the future of our society; for "as long as there is one upright man, as long as there is one compassionate woman...the scene is not desolate.""--